1987
DOI: 10.1207/s15327906mbr2204_1
|View full text |Cite
|
Sign up to set email alerts
|

Air Force Pilot Personality: Hard Data on the "Right Stuff"

Abstract: Three-hundred and fifty Air Force pilots undergoing Undergraduate Pilot Training were administered the Personality Research Form (PRF) and the Millon Clinical Multiaxial Inventory (MCMI) within the first four weeks of training. Pilots were significantly different from non-flying college students on several PRF scales. Cluster analyses indicated that three very distinct personality types exist in the data. These types were supported through multiple cross-validations. Descriptions of pilot personality types are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 7 publications
0
34
0
Order By: Relevance
“…While studies have found that aviators often report trait levels that distinguish them from the general public (Fitzgibbons et al, 2004), caution should be exercised in attempting to generalize one personality profile to all aviators (Retzlaff & Gibertini, 1987). A common finding is that aviators seem to group around certain clusters of personality traits (Kanki & Palmer, 1993;Retzlaff & Gibertini).…”
Section: The Aviator Personalitymentioning
confidence: 99%
See 4 more Smart Citations
“…While studies have found that aviators often report trait levels that distinguish them from the general public (Fitzgibbons et al, 2004), caution should be exercised in attempting to generalize one personality profile to all aviators (Retzlaff & Gibertini, 1987). A common finding is that aviators seem to group around certain clusters of personality traits (Kanki & Palmer, 1993;Retzlaff & Gibertini).…”
Section: The Aviator Personalitymentioning
confidence: 99%
“…A common finding is that aviators seem to group around certain clusters of personality traits (Kanki & Palmer, 1993;Retzlaff & Gibertini). The conclusion has been that these clusters of traits can predict which aviators are likely to have the "right stuff' or the "wrong stuff' in terms of performance (Picano, 1991;Retzlaff & Gibertini).…”
Section: The Aviator Personalitymentioning
confidence: 99%
See 3 more Smart Citations